48‐2: Electronic Paper 2.0: Frustrated eTIR as a Path to Color and Video. Issue 1 (30th May 2018) - Fleming, Robert; Peruvemba, Sri; Holman, Robert; Ferguson, Scott; Sadlik, Bram; Johansson, Thomas
Abstract : Reflective display technologies including LCD, electrowetting, electrophoretic, and MEMS are being sought after in low power display applications. One of the major barriers to broad market adoption has been the difficulty in developing displays capable of video speeds and reflected brightness high enough to achieve full color. This paper will review the progress of a novel electrophoretic display capable of video level switching speeds and full color using low cost color filters.